2021
DOI: 10.1021/acsaelm.1c00057
|View full text |Cite
|
Sign up to set email alerts
|

Charge Transport through Functionalized Graphene Quantum Dots Embedded in a Polyaniline Matrix

Abstract: Nitrogen-functionalized graphene quantum dots embedded in a polyaniline matrix (NGQD–PANI) are extremely promising candidates for the development of next-generation sensors and for thermoelectric materials design with the distinct advantage of tunability of electronic properties by controlled doping and/or by controlling the inherent disorder in the microstructure. While their application is increasing in photovoltaics, energy storage, and sensing technologies, a clear understanding of conduction in these hybr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 69 publications
0
15
0
Order By: Relevance
“…Variables such as the size and shape of the NZF nanostructures, the degree of dispersion, and the kinds of interaction and interface between the organic and inorganic phases, among others, have a direct influence on properties such as conductivity, piezoresistivity, and photocurrent. 31 Previously reported results of graphene quantum dots in a polyaniline matrix, 23 ZnO nanorods assisted with polyaniline, 26 2D self-healable polyaniline-polypyrrole nanoflakes, 27 and in-situ conformal coatings of polyaniline on GaN microwires 28 showed that different experimental routes can be successful in producing organic-inorganic hybrids of polyaniline. Iron, with its low elemental cost, high earth-abundance, and environmentally benign character, has broadened the scope for material development and is a suitable material for constructing next-generation technology.…”
Section: Introductionmentioning
confidence: 98%
See 4 more Smart Citations
“…Variables such as the size and shape of the NZF nanostructures, the degree of dispersion, and the kinds of interaction and interface between the organic and inorganic phases, among others, have a direct influence on properties such as conductivity, piezoresistivity, and photocurrent. 31 Previously reported results of graphene quantum dots in a polyaniline matrix, 23 ZnO nanorods assisted with polyaniline, 26 2D self-healable polyaniline-polypyrrole nanoflakes, 27 and in-situ conformal coatings of polyaniline on GaN microwires 28 showed that different experimental routes can be successful in producing organic-inorganic hybrids of polyaniline. Iron, with its low elemental cost, high earth-abundance, and environmentally benign character, has broadened the scope for material development and is a suitable material for constructing next-generation technology.…”
Section: Introductionmentioning
confidence: 98%
“…); therefore, they are applied in a wide variety of technological devices such as memory, display and telecommunication devices. [19][20][21][22][23] Currently, organic conductive polymers such as polyaniline, 19,20,24 polypyrrole, 21,22 polyacetylene, 23,25 polythiophene, and poly(3,4-ethylene dioxythiophene) 26,27 are preferred for fabricating flexible devices and have been gaining huge attention due to their unique properties, such as lowcost, easy processing and eco-friendliness. 22,23 An important class of hybrid materials is those in which the organic fractions are composed of conducting polymers such as polyaniline and polypyrrole.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations